A Randomized Internet-Based Pilot Feasibility and Planning Study of Cherry Extract and Diet Modification in Gout. Issue 4 (June 2020) - Singh, Jasvinder A.; Green, Candace; Morgan, Sarah; Willig, Amanda L.; Darnell, Betty; Saag, Kenneth G.; Weiss, Rick; Cutter, Gary; McGwin, Gerald
Abstract : Objective: The aim of this study was to conduct a 9-month pilot Internet randomized controlled trial (RCT) of cherry extract and diet modification in gout to assess the feasibility of an Internet study and obtain effect estimates. Methods: After providing online informed consent in response to Internet advertisements and social media or clinic flyers, 84 people with physician-confirmed gout were randomized to either cherry extract 3, 600 mg/d (n = 41) or dietitian-assisted diet modification for gout (n = 43). All study outcomes were collected via Internet and phone calls. The primary objective was the feasibility of an Internet study, and secondary objectives were to obtain effect estimates for gout flares, functional ability assessed with the Health Assessment Questionnaire (HAQ), and adverse events (AEs) for future trials. Results: Of the 84 people randomized, overall completion rates were more than 80% for most study procedures up to 6 months and similar for the 2 active comparators. Improvements were seen in gout flares and HAQ scores in cherry extract and diet modification groups at 9 months compared with baseline: gout flares per month, 0.22 versus 0.36 ( p = 0.049) and 0.28 versus 0.31 ( p = 0.76); proportion with any gout flare, 56% versus 98% ( p < 0.0001) and 65% versus 98% ( p = 0.0002); and mean ± standard deviation HAQ score, 0.28 ± 0.54 versus 0.55 ± 0.68 ( p = 0.001) and 0.23 ± 0.40 versus 0.48 ± 0.61 ( p = 0.06), respectively. Any AEs and gastrointestinal symptoms/AEs at 9 months in cherry extract and diet modification groups were 3% versus 0% and 28% versus 27%, respectively. Conclusions: An Internet gout RCT is feasible for nonpharmacological gout treatments. A hypothesis-testing, large Internet RCT of cherry extract versus placebo is needed. Abstract : In this internet-based study, 84 gouty patients were randomized to receive either a cherry extract or a diet modification. The cherry extract group appeared to have less flares over the ensuing follow up period and better function. Side effects were negligible. This study reaffirms the feasibility of conducting large clinical trials using this methodology.Supplemental digital content is available in the text.